Optimalisasi Limbah Kain Perca Sebagai Kerajinan Keset Kelompok Pkk Di Desa Ngade Kanigoro Blitar - Irawan, Dani; Hendarti, Devina Rosha; Bisono, Rahayu Mekar (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this community service activity is to provide the skills and tools available to produce mats to PKK groups in Ngade Kanigoro Blitar Village so that it will affect the process, (2) The method used in this PKM activity is community empowerment through training and accompaniment. (3) The results of this activity are in the form of providing skills in the utilization of existing patchwork waste raw materials in accordance with what partners need optimally so that the smooth process of cassette production can be maximized and the desired design is in accordance with expectations and provides a tool for making mats. (4) The conclusion of this activity is the empowerment of the PKK group through training on making mats from cloth waste in the Empowerment and Family Welfare (PKK) group of Ngade Village, Kanigoro District, Blitar Regency, namely increasing knowledge, increasing skills, and increasing the attitude of learning citizens.